Prototype of a Warehouse Shoe Lamp Automation System Using Motion Sensors Based on the Internet of Things (IoT) - Pandu Mardya Wijaya; Abdi Pandu Kusuma; Rizki Dwi Romadhona (Universitas Islam Balitar, 2024)
This research presents the design and development of a monitoring and control system for warehouse lighting using the SR501 passive infrared (PIR) motion sensor, which is based on the Internet of Things (IoT). The goal of this research is to improve the comfort, efficiency, and security of the Jeensneakers Shoe Warehouse in Kedawung, Nglegok, Blitar. By introducing IoT-based automatic lights accessed through a smartphone, users can monitor and control the lights remotely, making lighting usage more effective and efficient. The research employs a prototype design using ESP32 and PIR sensors, conducted through survey methods, observations, and interviews. The testing results show that the automatic lights can be controlled remotely using a smartphone, and the motion sensor can function as a security feature for the Jeensneakers shoe warehouse. The evaluation of the IoT-based automatic lighting system was considered feasible, with an 80% acceptance rate from experts, indicating a sufficient level of feasibility.